Evaluation of clay pot cooler storage for preserving postharvest quality of leafy vegetables - Weerahetti Arachchilage Hettiarachchi; Konara Mudiyanselage Sandarenu; Supurni Nimalshani Gamage; Rathnayake Mudiyanselage Attanayake; Yapa Mudiyanselage Dasanayaka; Dharshani Dammika Galahitiyawa; Herath Mudiyanselage Kumarihami (Journal of Horticulture and Postharvest Research, 2024)
Purpose: The effectiveness of the evaporative clay pot coolers was studied to preserve the postharvest quality of leafy vegetables, including kankun (Ipomoea aquatica), gotukola (Centella asiatica), lettuce (Lactuca sativa) and thampala (Amaranthus spp.). Research method: The bundles of leafy vegetables weighed about 200 g and were stored for seven days under room temperature storage, refrigerated storage, and clay pot cooler storage. Findings: The average temperatures were 27.7 °C, 7.1 °C, and 25.6 °C, and relative humidity values were 76.1%, 58.2%, and 93.6% in room temperature storage, refrigerated storage, and clay pot cooler, respectively. The average cooling efficiency of clay pot coolers was 66.7%. The physiological weight losses of leafy vegetables were significantly reduced during clay pot cooler storage. The chlorophyll content, soluble solids content, color changes, and visual quality of leafy vegetables were significantly maintained in clay pot cooler storage compared to room temperature storage. Research limitations: The main limitation of this study was the seepage of water into the inner pot of the clay pot cooler which enhanced the decay of leafy vegetables. This was successfully controlled by avoiding overwatering the sand that was used as the lining material of the clay pot cooler. Originality/Value: The clay pot cooler is one of the alternative low-cost storage methods to preserve the quality of leafy vegetables during storage.